Piracy and International and regional efforts to combat maritime piracy And the obstacles to combating it - عبدالله, ميلاد; رامي كاسر لايقه (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The crime of maritime piracy is a crime that threatens all of humanity, as some believe that it is a myth from the legends of the past, but its reality proves the opposite through the recent rise in piracy operations, which makes it one of the most prominent, and most important topics of the hour and one of the most heinous crimes that threaten the safety of maritime navigation, international trade as well as the lives of people, ships and property in many countries of the world. As this threat, which is increasing day by day, requires the attention of international law and international jurisprudence in order to combat and suppress this phenomenon and find solutions to combat it.